2012
DOI: 10.1128/mcb.06466-11
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Transcription Factor YY1 by CK2α Prevents Cleavage by Caspase 7 during Apoptosis

Abstract: In this report, we describe the phosphorylation of Yin Yang 1 (YY1) in vitro and in vivo by CK2␣ (casein kinase II), a multifunctional serine/threonine protein kinase. YY1 is a ubiquitously expressed multifunctional zinc finger transcription factor implicated in regulation of many cellular and viral genes. The products of these genes are associated with cell growth, the cell cycle, development, and differentiation. Numerous studies have linked YY1 to tumorigenesis and apoptosis. YY1 is a target for cleavage by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 70 publications
3
28
0
Order By: Relevance
“…CK2α is another kinase identified as constitutively phosphorylating YY1 at serine 118. This modification protects YY1 cleavage by caspase 7 during apoptosis [23]. Our lab also reported that phosphorylation of YY1 in the DNA binding domain (threonine 348 and threonine 378) during mitosis abolishes its DNA binding activity [7].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…CK2α is another kinase identified as constitutively phosphorylating YY1 at serine 118. This modification protects YY1 cleavage by caspase 7 during apoptosis [23]. Our lab also reported that phosphorylation of YY1 in the DNA binding domain (threonine 348 and threonine 378) during mitosis abolishes its DNA binding activity [7].…”
Section: Introductionmentioning
confidence: 68%
“…Multiple residues on YY1 are targets of post-translational modification, including, S-nitrosation [16], acetylation [17], [18], O-linked glycosylation [19], sumoylation [20], and poly(ADP-ribosyl)ation [21], [22], all of which regulate the function and activity of YY1. More recently, we identified and mapped multiple phosphorylation sites in YY1, including, threonine 39, serine 118, serine 247, threonine 348 and threonine 378 [7], [23][25]. The first kinase proven to phosphorylate YY1 in vivo was Plk1, which phosphorylates threonine 39 during G2/M stage of the cell cycle [25].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of threonine T58 at the P2 position in the caspase recognition motif by CKII or CKI prevents human Bid cleavage by caspase-8 (65). Phosphorylation of YY1 by CKII␣ prevents cleavage by caspase-7 during apoptosis (66). CKII phosphorylation during virus infection plays an important role in regulation of ICP27 and EB2 binding activities to cellular cofactors and promotes virus replication of HSV-1 and EBV (63,67,68).…”
Section: Discussionmentioning
confidence: 99%
“…2A) show that caspase substrates, including Bid, which promotes apoptotic progression when it is cleaved, can be phosphorylated by CSNK2 at sites adjacent to caspase cleavage sites. Because phosphorylation adjacent to caspase cleavage sites blocks cleavage, these observations suggest that increased phosphorylation by CSNK2 could promote cell survival by inhibiting caspase action (9)(10)(11)(12)(13)(14).…”
Section: Convergence Of Csnk2 With Caspase Pathwaysmentioning
confidence: 99%